Konstribusi Mahasiswa Dalam Peningkatan Literasi Numerasi Melalui Kegiatan Kampus Mengajar di SDN 028 Balikpapan Tengah - Charisma Azizah Ibrahim; Ameliana Ameliana; Hendra Saputra Philippus; Norjannah Norjannah; Gyta Krisdiana Cahyaningrum; Didik Cahyono (Lembaga Pengembangan Kinerja Dosen, 2024)
The campus teaching program is a form of program to build collaboration between students and teachers to support the educational process in schools. This service method is a qualitative approach. The location for community service was carried out at SDN 028 Balikpapan Tengah, participants in this activity included students and teachers. Data collection uses observation, interview and documentation techniques. The results of community service through the contribution of the 6th class of teaching campus students explained that the implementation of the program for implementing numeracy literacy included: integration of literacy, numeracy and technology adaptation (SI 3), literacy and numeracy classes, cognitive and non-cognitive assessments, adaptation technology with the theme